Teaching Mathematics in Teacher Training: Difficulties and challenges - Riesco Hernández, Pilar (Pulso. Revista de educación, 2001)
The subject of mathematics, being a fundamental component of the teaching curriculum across many disciplines, poses significant challenges when it comes to teaching, owing to the varied levels of knowledge and skills among students upon their admission to university level studies. This article seeks to explore the learning objectives that aspiring teachers should strive for, both in terms of mathematical content and teaching methodologies.